Pengaruh Teknologi Terhadap Hukum Dagang di Indonesia - Anastasya Agustine; Nadya Septiani; Chindy Nurul f; Ayu Salsabila (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
Technological advances have had a major impact on the development of tradelaw. This applies in Indonesia. Information and communication technology, especially the Internet, has changed the way trade is conducted from traditional to digital or e-commerce methods. Thiscreatestheneedfor legal regulationsthattakeintoaccountnewtrendssuch as personal data protection, electronic transaction security, the validity of digital documents, and consumer protection in the digital space. The enactment of the Electronic Transaction Information Law (UU ITE) and laws and regulations in the field of electronic commerce, such as Government Regulation Number 80 of 2019 (PMSE), is clear evidence that trade law is adapting to technology. Furthermore, technological development also encourage the emergence of blockchain-based smart contracts, which require legal recognition and adaptation of their validity. However, the impact of this technology also creates challenges such as the digital divide, lack of legal literacy among SMEs, and challenges of cross-border law enforcement in international transactions. Therefore, building an inclusive, technologically sensitive, and adaptive commercial legal system requires synergy between regulators, economicactors, and the community.